A 2-Step Laemmli and Antigen Retrieval Method Improves Immunodetection. Issue 6 (July 2016) - Scalia, Carla R.; Gendusa, Rossella; Cattoretti, Giorgio
Abstract : Detection by immunohistochemistry of antigens relies on reproducibly optimal preanalytical and analytical variables such as fixation conditions, antigen retrieval (AR), and the resolutive power of the detection system. There is a need to improve immunodetection on routinely fixed and embedded material, particularly for scarcely represented but relevant antigens. We devised a 2-step method and applied it to a panel of antigens of common use for diagnosis, prognosis, individualized therapy use, or research. The first step consists of a 10 minutes. Incubation at 95°C with a modified Laemmli extraction buffer. This was followed by a traditional AR method. Detection of the vast majority of antigens was improved over a simple AR with preservation of tissue integrity, as shown by quantitative image analysis. The mechanism underlying the improved detection may be controlled denaturation followed by heat-mediated retrieval, a method we dubbed "antigen relaxing" and which will improve routine detection of scarce antigens in formalin-fixed, paraffin-embedded material. Abstract : Supplemental Digital Content is available in the text.